Immediate intermittent compression over vascular anastomosis: a new technique to prevent thrombosis? - Balduino Ferreira de Menezes; Matheus Scuracchio Fernandes; Lucas Vannuchi Magnani; Fausto Viterbo (Revista Brasileira de Cirurgia Plástica, 2024)
Introduction: This study aims to evaluate the effect of immediate intermittent compression on microsurgical arterial anastomoses in comparison with fixed compression and only observation in an experimental laboratory. Methods: The two femoral arteries of twelve male Wistar rats were sectioned and reanastomosed to compare patency at 30 minutes and 7 days. Group I: immediate intermittent compression was performed over the anastomosis for 60 s; group II: a fixed compression was maintained immediately after the anastomosis for 60 s; group III: after completion of the anastomosis, no additional intervention was performed. In addition to the patency assessment, the animals were weighed and the operated arterial diameters were measured. Results: Twenty-four femoral arteries were examined. Initial average weights of the rats in groups I, II, and III were 243.8g, 254.6g, and 260.4g, respectively, while the final weights were 264.4g, 281g, and 282.1g (p<0.001), respectively; mean diameter of the approached arteries was 0.89, 0.88, and 0.90mm, respectively, and the anastomoses (time in minutes) were 25.6, 24.5, and 24.5, respectively; final patencies after 7 days were 62.5% (p=0.07), 25% (p=0.48), and 50% (p=0.13), respectively. Conclusion: Immediate intermittent compression can be performed at the end of microsurgical arterial anastomoses without affecting the final patency of the procedure.